Simulation of Land Movement Detection System Using Accelerometer Sensors and Fiber Optic - Qonitatul Hidayah; Umi Salamah; Yuda Wiges Pratama (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2022)
Indonesia’s geographical conditions are one of the causes of land movement. This land movement can occur due to the movement of rock masses, soil, or debris material making up the slopes. The stability of a slope is influenced by several parameters such as material, soil strength, slope angle, climate, vegetation, and time. In Indonesia, land movement disasters are placed the third rank of natural disasters that occurred throughout 2021. Thus, the development of a land movement detection system is very important for monitoring land movement disasters. In this research, a land movement detection device was developed using the ADXL 335 accelerometer sensor and fiber optic. For data acquisition, Arduino Uno, LEDs, and photodetectors were used. Arduino Uno was used to convert analog signals to digital. In addition, LEDs were used as light sources, and photodetectors were used as a receiver. Changes in the output voltage due to macrobending loss are obtained when the curvature changes due to the pendulum system. The results of the study show that the average acceleration values on the x, y, and z axes of the accelerometer sensor are 0.118 g, 0.925 g, and -2.494 g. The maximum land displacement movement that can be represented by fiber optic is 4 cm. Further, the combination use of accelerometer sensors and fiber optic can show the magnitude of the force that causes displacement, the direction of land displacement, and the magnitude of the land displacement that occurs.